Treatment of gastrointestinal stromal tumor with imatinib mesylate: a retrospective single-center experience in Heidelberg - Kasper, Bernd; Kallinowski, Birgit; Herrmann, Thomas; Lehnert, Thomas; Mechtersheimer, Gunhild; Geer, Thomas; Ho, Anthony Dick; Egerer, Gerlinde (Digestive diseases, 2006)
BACKGROUND: Gastrointestinal stromal tumor (GIST) is the most common mesenchymal neoplasm of the gastrointestinal tract. Surgery has been the only effective therapy. However, many patients still eventually die of disease recurrence. Chemotherapy and radiation therapy have been of limited value. Imatinib mesylate (Glivec) is an orally administered competitive inhibitor of tyrosine kinases associated with the KIT, ABL protein, licensed for the treatment of metastatic GIST since 2002 in Germany. - METHODS: We summarized the data of 16 patients with advanced or metastatic GIST treated with imatinib mesylate in palliative and neoadjuvant settings. - RESULTS: Overall response was 81%, with no evidence of disease (NED) in 3/16 (19%), partial response (PR) in 9/16 (56%) and stable disease (SD) in 1/16 (6%), whereas 3/16 patients (19%) suffered from progressive disease (PD). Mean follow-up was 18.6 months [range: 4-30]. Mean progression-free survival (PFS) was 17.6 months [range: 0-30], mean overall survival (OS) from initial diagnosis was 32.3 months [range: 5-122]. Most common side effects were periorbital edema and skin rash. - CONCLUSION: Imatinib mesylate is well tolerated in a dose of up to 800 mg/day and has significant activity during long- term treatment of patients with advanced or metastatic GIST.